2010
DOI: 10.1073/pnas.1005817107
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone-induced anisotropy in yeast plasma membrane phosphatidylinositol-4,5- bis phosphate distribution is required for MAPK signaling

Abstract: During response of budding yeast to peptide mating pheromone, the cell becomes markedly polarized and MAPK scaffold protein Ste5 localizes to the resulting projection (shmoo tip). We demonstrated before that this recruitment is essential for sustained MAPK signaling and requires interaction of a pleckstrin homology (PH) domain in Ste5 with phosphatidylinositol 4,5-bisphosphate [PtdIns (4,5)P 2 ] in the plasma membrane. Using fluorescently tagged highaffinity probes specific for PtdIns(4,5)P 2 , we have now fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 36 publications
8
104
3
Order By: Relevance
“…Finally, the phosphatidylinositol 3-kinase Vps34 promotes activation of Fus3 but not Kss1 (88). With the exception of Ste5, however, there is little evidence that these regulators are subject to dynamic regulation by pheromone stimulation (86). In contrast, ubiquitination of Ste7 is strictly dependent on pheromone stimulation and subsequent phosphorylation by Ste11 (33).…”
Section: Cdc4mentioning
confidence: 90%
“…Finally, the phosphatidylinositol 3-kinase Vps34 promotes activation of Fus3 but not Kss1 (88). With the exception of Ste5, however, there is little evidence that these regulators are subject to dynamic regulation by pheromone stimulation (86). In contrast, ubiquitination of Ste7 is strictly dependent on pheromone stimulation and subsequent phosphorylation by Ste11 (33).…”
Section: Cdc4mentioning
confidence: 90%
“…It has been shown that polarized PI(4,5)P 2 in the plasma membrane interacts with the pleckstrin homology (PH) domain in Ste5 to cluster Ste5 (Winters et al 2005;Garrenton et al 2006Garrenton et al , 2010 and that ergosterol promotes PI(4,5)P 2 polarity ( Jin et al 2008). To determine whether the sterol trafficking defects in arv1 cells contribute to defects in PI(4,5)P 2 polarization in response to pheromone, we examined the localization of GST-GFP-PH PLCd after treating cells with a-factor.…”
Section: Q59lmentioning
confidence: 99%
“…The Ste5 scaffolding protein recruits the MAP kinases Ste11, Ste7, and Fus3 in response to pheromone to initiate signaling. In turn, Ste5 is recruited to the plasma membrane by pheromone/receptor binding and subsequent interaction with the Gbg dimer Ste4-Ste18, but also interacts with phosphatidyinositol 4,5-bisphosphate [PI(4,5)P 2 ] in the plasma membrane through its pleckstrin homology (PH) domain (Winters et al 2005;Garrenton et al 2006Garrenton et al , 2010. Activation of the pheromone response pathway results in G1 cell cycle arrest, mating-specific gene transcriptional induction, and changes in cytoskeletal structure, which allows for polarized cell growth and alterations in nuclear architecture, ultimately leading to cell fusion and formation of an a/a diploid (Wang and Dohlman 2004).…”
Section: T He Budding Yeast Saccharomyces Cerevisiae Is Viablementioning
confidence: 99%
See 2 more Smart Citations